2022
DOI: 10.3389/fnhum.2021.781554
|View full text |Cite
|
Sign up to set email alerts
|

General Psychopathology, Cognition, and the Cerebral Cortex in 10-Year-Old Children: Insights From the Adolescent Brain Cognitive Development Study

Abstract: General psychopathology and cognition are likely to have a bidirectional influence on each other. Yet, the relationship between brain structure, psychopathology, and cognition remains unclear. This brief report investigates the association between structural properties of the cerebral cortex [surface area, cortical thickness, intracortical myelination indexed by the T1w/T2w ratio, and neurite density assessed by restriction spectrum imaging (RSI)] with general psychopathology and cognition in a sample of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Inverse correlations were also observed between local T1w/T2w ratio and more specific aspects of cognition, ranging from attention, inhibition and language to working memory [36]. At the same time, a recent study [39], based on the same dataset as the present work, only found one statistically significant association between T1w/T2w ratio and a composite score of cognitive performance in an atlas-based analysis. One conceivable cause behind this discrepancy is the different age groups that were investigated in the studies.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Inverse correlations were also observed between local T1w/T2w ratio and more specific aspects of cognition, ranging from attention, inhibition and language to working memory [36]. At the same time, a recent study [39], based on the same dataset as the present work, only found one statistically significant association between T1w/T2w ratio and a composite score of cognitive performance in an atlas-based analysis. One conceivable cause behind this discrepancy is the different age groups that were investigated in the studies.…”
Section: Discussionsupporting
confidence: 59%
“…Research on the relationship between T1w/T2w ratio maps and behavioral data in humans is limited, but some reports exist in the literature that link the measure to various cognitive abilities across a wide range of ages [35][36][37][38][39]. The T1w/T2w contrast has also been applied within clinical and affective neuroscience [40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The exception was cortical thickness, where we found a weak negative association, indicating that having a thicker cortex was linked to better cognitive performance. Prior studies have supported a relationship between cognitive performance and surface area in 10-year-old children ( Patel et al, 2022 ), and white matter DTI in both the PNC sample ( Tang et al, 2017 ) and during childhood and adolescence ( Goddings et al, 2021 ). Studies assessing the link between cognition and cortical thickness have revealed mixed results, with some reporting a positive association ( Burgaleta et al, 2013 , Choi et al, 2008 , Karama et al, 2013 , Karama et al, 2011 ), and others no significant associations ( Tamnes et al, 2011 ).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, it is worth noting that psychopathology severity (e.g., levels of anxiety, depression and so on) has not been systematically accounted for in the reviewed studies examining associations with cognitive function. Psychopathology severity impacts cognitive function (Chavez-Baldini et al 2021) but also brain structure properties particularly in the developing brain (Patel et al 2022;Mattoni, Wilson, and Olino 2021;Romer, Ren, and Pizzagalli 2023). Recently, cerebellar structure has been shown to be linked to both general cognitive function and psychopathology (Moberget et al 2019).…”
Section: Introductionmentioning
confidence: 99%